2022
DOI: 10.1038/s41598-022-11405-3
|View full text |Cite
|
Sign up to set email alerts
|

Preyssler-type phosphotungstate is a new family of negative-staining reagents for the TEM observation of viruses

Abstract: Transmission electron microscopy (TEM) is an essential method in virology because it allows for direct visualization of virus morphology at a nanometer scale. Negative staining to coat virions with heavy metal ions must be performed before TEM observations to achieve sufficient contrast. Herein, we report that potassium salts of Preyssler-type phosphotungstates (K(15-n)[P5W30O110Mn+], M = Na+, Ca2+, Ce3+, Eu3+, Bi3+, or Y3+) are high-performance negative staining reagents. Additionally, we compare the staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…[ 1 , 2 , 3 ] These properties have led to their wide use as the main compounds in catalysts,[ 4 , 5 ] electrocatalysts,[ 6 , 7 ] medicines, [8] sensors, [9] and staining reagents. [ 10 , 11 ] Normally, polyoxometalates are synthesized via the condensation of oxoanions (MoO 4 2− , WO 4 2− , or VO 4 3− ) using a self‐assembly process. [ 1 , 12 ] The formation of polyoxometalates is influenced by experimental conditions, such as the type and concentration of component metals and counter‐cations, temperature, solvent, and pH of the solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 , 2 , 3 ] These properties have led to their wide use as the main compounds in catalysts,[ 4 , 5 ] electrocatalysts,[ 6 , 7 ] medicines, [8] sensors, [9] and staining reagents. [ 10 , 11 ] Normally, polyoxometalates are synthesized via the condensation of oxoanions (MoO 4 2− , WO 4 2− , or VO 4 3− ) using a self‐assembly process. [ 1 , 12 ] The formation of polyoxometalates is influenced by experimental conditions, such as the type and concentration of component metals and counter‐cations, temperature, solvent, and pH of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalates form a wide variety of compositions and structures that produce different physical and chemical properties, such as negative charges, oxo‐enriched surfaces, acid‐base properties, and redox potential [1–3] . These properties have led to their wide use as the main compounds in catalysts, [4,5] electrocatalysts, [6,7] medicines, [8] sensors, [9] and staining reagents [10,11] . Normally, polyoxometalates are synthesized via the condensation of oxoanions (MoO 4 2− , WO 4 2− , or VO 4 3− ) using a self‐assembly process [1,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic macrocyclic polyanions belong to an underestimated class of compounds which can be utilized in different areas of modern coordination chemistry. Cadot et al presented [Mo 154 O 462 H 14 (H 2 O) 70 ] 14– as a building block of a hierarchically organized supramolecular system containing smaller POM/cluster and γ-cyclodextrin molecules. , Cronin et al reported systematic studies regarding giant (nanosized) cyclic molybdates. In the case of polytungstates, there are medium-sized cavitands such as Preyssler-type [X n + P 5 W 30 O 110 ] (15–n)– , , [P 8 W 48 O 184 ] 40– ( {P 8 W 48 } ), [NaSb 9 W 21 O 86 ] 18– , , [NaAs 4 W 40 O 140 ] 27– and so on.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Cronin et al reported systematic studies regarding giant (nanosized) cyclic molybdates. 36−39 In the case of polytungstates, there are medium-sized cavitands such as Preyssler-type [Xn + P 5 W 30 O 110 ] (15−n)− , 40,41 In particular, the [P 8 W 48 O 184 ] 40− has been utilized as a multifunctional platform for different applications like functionalization 45,46 or materials preparation. 47,48 Recently, a new class of compounds based on the {P 8 W 48 } building block called POMzites has been announced.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The POM family exhibits properties such as multi-electron redox activity, acidic property, photochemistry, and magnetism, and has been applied in many fields of functional materials, such as catalysts, conducting materials, and magnetic materials. [1,2] Among the wide class of POMs, Preyssler-type phosphotungstates have been attracting significant attention, and they have been applied as catalysts, [3][4][5][6][7][8][9][10][11][12] single-molecule electret materials, [13] single-molecule magnetic materials, [14] conductive materials, [15][16][17][18][19][20][21][22][23] staining reagents, [24] antitumor activity, [25] liposome collapse reagents, [26] and antibacterial agents. [27][28][29][30] The Preyssler-type phosphotungstates, [P 5 W 30 O 110 Z n + (H 2 O)] (15À n)À , are constructed using five PO 4 tetrahedra surrounded by thirty WO 6 octahedra, which create a doughnut-shaped structure with an internal cavity space that can encapsulate a cation (Z n + ) in the molecule (Figure 1).…”
Section: Introductionmentioning
confidence: 99%